Carga de trabalho de equinos da raça Quarto de Milha monitorados com Sistema de Posicionamento Global (GPS) e monitor cardíaco durante exercício de Três Tambores - Carvalho, Marina Gonzales de [UNESP] (2015)
The objective was to determine the workload through the speed and heart rate (HR), and the influence of Barrel Racing exercise on blood parameters of Quarter Horses (QH). 20 adult horses QH, 6.6 ± 2.5 years age and 462.8 ± 34.2 kg, were monitored during the Barrel Racing exercise, with the use of GPS and HR monitor. In the moments before and after exercise (three, five, 10 and 30 min) were determined: packed cell volume (PCV), total plasma protein (TPP), lactate and glucose. Along the way were measured distance, the time, the calculated average speed (CAS), the average speed obtained by GPS (ASGPS) and HR. The animals ran 144.0 m in 19.045 s to complete the route. The CAS was 7.6 m/s. The route segment in which the set (horse / rider) showed the highest CAS was the final stretch. The segment with smaller CAS was the outline on the 1st barrel. The ASGPS was below CAS. HRaverage was 195 bpm and the peak was 211 bpm on the way. In this mode, horses predominantly use anaerobic metabolism to perform the exercise. The use of four sensors pairs photocell on route make allow to evaluate the performance of horses in this mode. To determine the horse's speed with the use of GPS equipment it should be considered the route and the accuracy of the equipment. The exercise influenced blood parameters according to exercise intensity